DEPICTION OF HERO-HEROINE AND NATURE IN RAJASTHANI PAINTING - Dhama, Shalini (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Early Rajasthani paintings are available in the 16th century. The main themes of these paintings are Krishna-leela, Nayika-bhed and Ragamala. Rajasthani painters have taken paintings based on the world of imagination rather than the visual world. In this era, the development of regional styles begins in which the styles of Mewar, Nathdwara, Bundi, Kishangarh, Bikaner, Jodhpur, Jaipur etc. are prominent. Each branch has some local specialty of its own due to which their paintings are recognized as different from the paintings of other styles.